Intelligent mesh material capable of adjusting liquid permeability in real time and preparation method thereof

By growing a polymer cilia array with magnetic response characteristics on the surface of the mesh material and adjusting the deflection angle of the cilia by using a magnetic field, the real-time and response hysteresis problems of liquid permeability adjustment in the prior art are solved, and efficient and continuous liquid permeability adjustment is achieved.

CN115531979BActive Publication Date: 2025-04-08GUANGDONG TECHNION ISRAEL INST OF TECH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202211133605.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-16
Publication Date
2025-04-08
Estimated Expiration
2042-09-16

AI Technical Summary

Technical Problem

The prior art is difficult to adjust the permeability of liquids through the grid in real time and effectively, and there are problems of response hysteresis and limited adjustment range.

Method used

By growing a polymer cilia array with magnetic response characteristics on the surface of the mesh material, and adjusting the deflection angle of the cilia using a magnetic field, thereby adjusting the penetrating porosity of the droplets, real-time adjustment of the liquid permeability and filtration speed is achieved.

Benefits of technology

Real-time and continuous adjustment of liquid permeability is achieved without response time, the adjustment range is large, and it is efficient and real-time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 220916154453
    Figure 220916154453
  • Figure 220916154500
    Figure 220916154500
  • Figure 220916154506
    Figure 220916154506
Patent Text Reader

Abstract

The present invention relates to a smart mesh material capable of adjusting liquid permeability in real time and a method for preparing the same. The smart mesh material is based on a mesh material, and its surface is modified with a magnetically responsive cilia array. The inclination angle of the cilia on the mesh surface is controlled by the action of a magnetic field to adjust the porosity through which droplets can pass, thereby achieving real-time control of liquid penetration. The present invention also provides a method for preparing the above-mentioned smart mesh material. The liquid penetration regulating mechanism of the smart mesh material of the present invention is adjusted by the deflection angle of the magnetically induced cilia under the action of a magnetic field. This mechanism for regulating liquid penetration is active; it has real-time and high efficiency in regulating liquid penetration, and has a large adjustment range for droplet permeability, with a change value of up to 5 times. The method for preparing the smart mesh material of the present invention is simple, time-saving, and can be applied over a large area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional materials and fluid control, and in particular relates to an intelligent mesh material for liquid penetration control and a preparation method thereof. Technical Background

[0002] Meshes and textiles are widely used in industry for atomization, spray cooling, mask and clothing manufacturing, etc. The liquid permeability of meshes, such as permeation threshold velocity and permeation quality, directly affects their application performance. However, current meshes are rigid and do not allow their shape to be changed or controlled, which means that the geometry of the mesh (pore size, spacing and density) is not adjustable. This defect greatly limits the application of meshes, where liquid permeability cannot be adjusted in real time to meet customized needs.

[0003] At present, there are two main technical methods for preparing meshes that control liquid permeability. One is to adjust the wettability of the mesh. The principle is that the various components that make up the mesh have different wettabilities. The hydrophilic components are conducive to liquid penetration, while the hydrophobic components hinder liquid penetration. The permeability of the liquid can be controlled by adjusting the contact between the components with different wettabilities and the liquid. However, this technology requires manual adjustment of the contact between the different components of the mesh and the liquid to increase or decrease the permeability of the liquid; this technology can only adjust the permeability of the liquid within a small range by relying solely on the change in the wettability of the mesh surface. The other is to adjust the size and geometric morphology of the mesh. The principle is that the main components that make up the mesh have special physical properties, which make it have a certain active responsiveness, such as expansion when exposed to water, extension at high temperature, etc. These deformations will change the size of the mesh and thus change the porosity of the mesh, and change the permeability of the liquid by changing the porosity. However, most grids used in industry or daily life are rigid structures that are difficult to deform. Even relatively flexible polymer grids and fabrics have limited deformation, so the application scope of this technology is limited and it cannot effectively adjust the permeability of liquids. Most importantly, although the liquid penetration control under this technology is a self-response to the environment, it takes a certain amount of time and has a certain lag, that is, it cannot achieve real-time control of liquid penetration, and the action time is limited.

[0004] Patent US 11,122,846 B2 discloses a fabric whose mesh pores can be changed according to the change of environmental humidity to adjust its own moisture permeability, but the moisture permeability ratio can only be adjusted by 0.56 times.

[0005] Patent US 6,770,579 B1 discloses a porous membrane in which the pore size changes due to different strains caused by the difference in wettability of different components in the composite material, but the mesh permeability cannot be continuously adjusted and has the defect of delayed response.

[0006] Patent US 2008 / 0057809 discloses a fiber coated with hydrogel on the surface, which can expand as the temperature decreases or the humidity increases, thereby reducing the permeability of the textile. However, this is only applicable to environments with large temperature differences and moisture changes, and the response has a lag and the adjustable range is limited.

[0007] Patent US 8389100 B2 discloses a fabric that uses the thermal elongation difference of polymers to cause multi-component fibers to bend or curl, thereby changing the permeability of the material. However, this is only applicable to environments with large temperature differences, and the permeability change brought about by only slight deformation of the fibers is very limited.

[0008] Patent CN 109371680 A discloses a humidity-sensing self-regulating fabric and its preparation method, in which the structure of the composite fabric automatically adjusts its curvature according to the change of environmental humidity, thereby changing the air permeability. However, this is only applicable to humidity changes and cannot continuously adjust the air permeability.

[0009] Patent CN 208959525 U discloses an industrial filter collector, which can only perform the filtering function by relying solely on the pores of the material itself.

[0010] Patent CN 113665194 A discloses a waterproof and breathable composite mesh and its preparation method and application. The permeability is passively adjusted by using layered meshes with different pore sizes and wettability. The multi-layer mesh actually leads to reduced air permeability and increased raw material costs.

[0011] In summary, the technical difficulties currently exist include how to control the liquid penetration through the mesh in real time, that is, how to "open" and "close" the liquid penetration through the mesh at any time without response time; and how to effectively adjust the amount of liquid penetration through the mesh, that is, when the droplets pass through the mesh, the transmittance can be adjusted quickly and continuously, and the adjustment range is large. Summary of the invention

[0012] In view of the difficulties in the prior art, the present invention provides an intelligent mesh material that can adjust liquid permeability in real time. By changing the porosity of the mesh that can be penetrated by droplets through a magnetic field, real-time adjustment of liquid permeability and filtration speed can be achieved.

[0013] The technical solution of the present invention is: an intelligent mesh material that can adjust liquid permeability in real time, with a mesh material as the substrate, and a polymer cilia array with magnetic response characteristics grown on its surface. The deflection angle of the cilia on the mesh surface, that is, the coverage rate of the cilia on the mesh holes, is adjusted by the action of the magnetic field, and then the porosity size that droplets can penetrate is adjusted to achieve real-time control of the mesh over liquid penetration.

[0014] The length of the magnetically responsive cilia is 500-3000um, the diameter is 30-200um, and the distance between the tips of two adjacent cilia is 30-700um.

[0015] Furthermore, the magnetically responsive cilia are curable polymers wrapped with magnetic micro / nanoparticles, and the polymer cilia formed after curing and molding have a hydrophobic modified coating on the surface of the cilia.

[0016] Preferably, the magnetic micro / nano particles are carbonyl iron powder particles, carbonyl cobalt particles or other particles with magnetic response characteristics, and the particle size is not greater than 20 um.

[0017] Preferably, the curable polymer is one or more viscoelastic polymers such as polydimethylsiloxane (PDMS), polyimide (PI), and polyurethane elastomer (TPU).

[0018] The present invention also provides for the first time a method for preparing an intelligent mesh material capable of adjusting liquid permeability in real time, which specifically comprises the following steps:

[0019] Step 1, mesh material preparation: the mesh material is ultrasonically cleaned with acetone and surfactant solution to remove surface impurities and oil stains, and then washed with deionized water and dried for later use;

[0020] Step 2: Prepare a curable polymer solution of magnetic micro / nanoparticles as a precursor solution: add 7.5 g of magnetic micro / nanoparticles to 15 g of solvent, perform ultrasonic dispersion treatment for 30 min at room temperature and then mechanically stir for 20 min, then add 5 g of curable polymer while stirring, and continue stirring for 10 min after the addition to obtain a precursor solution;

[0021] Step 3: Place the grid material obtained in step 1 horizontally on the surface of a magnet, apply the prepared precursor solution to the surface of the grid material by spraying, spin coating or dipping, and the curable polymer solution containing magnetic micro / nanoparticles grows directionally on the grid surface in a self-assembled manner along the magnetic induction lines under the action of the magnetic field, forming a sample with a cilia-like magnetic induction array structure on the grid surface; place the sample and the magnet in an oven at 60°C to remove the solvent and pre-cure for 60 minutes, then remove the magnet, and cure the sample at 120°C for 60 minutes to obtain a cilia array with magnetic response characteristics grown on the surface of the grid material;

[0022] Step 4, hydrophobically modify the magnetically responsive ciliary array obtained in step 3: add 0.2g of fluorinated silane, 0.1g of silane coupling agent and 0.1g of hydrophobic nanoparticles to 10g of organic solvent respectively, mechanically stir for 30min and then ultrasonically treat for 30min at room temperature to obtain a hydrophobic modified solution, use a spraying method to hydrophobically modify the surface of the solidified ciliary array, and then dry it at 80°C for 60min to finally obtain a smart grid with a magnetically responsive ciliary array modified on the surface.

[0023] Furthermore, the solvent in step 2 is one of toluene, dichloromethane, chloroform and n-hexane.

[0024] Furthermore, the mesh material described in step three is a rigid mesh material including laser-processed or commercial aluminum mesh, copper mesh, stainless steel mesh, or a flexible mesh material such as polymer mesh, fiber mesh and fabric. The mesh morphology is circular, square, or triangular. The pores allow droplets to penetrate. The diameter of the hole and the distance between the geometric centers of two adjacent holes are 100~1000um.

[0025] Furthermore, the magnet described in step three is a permanent magnet of neodymium iron boron, samarium cobalt, or aluminum nickel cobalt, and can be in the shape of a cuboid, a cube, or a cylinder, and has a magnetic induction intensity of 0.1 to 2T.

[0026] Furthermore, in step three, when the spraying method is adopted, the angle between the nozzle direction and the horizontal plane of the sample is 0~90°, that is, the nozzle direction can be horizontal, vertical or a certain angle with the sample, the distance between the nozzle and the sample is 5~50cm, the spraying pressure is 1~5bar, and the spraying volume is 2~10mL.

[0027] Furthermore, in step 4, in the hydrophobic modified solution, the hydrophobic nanoparticles are one of hydrophobic silicon dioxide, titanium dioxide, aluminum oxide and zinc oxide, and have a particle size of 5 to 500 nm; the fluorinated silane is 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane, 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane, trimethoxy (1H, 1H, 2H, 2H-perfluoro-1-octyl) One of silane and triethoxy (1H, 1H, 2H, 2H-perfluoro-1-octyl) silane; the silane coupling agent is one of 3-aminopropyltriethoxysilane (KH550), 3-(2; 3-epoxypropoxy)propyltrimethoxysilane (KH560) and N-[3-(trimethoxysilyl)propyl]ethylenediamine (KH792); the organic solvent is one of ethanol, propanol, ethyl acetate and toluene.

[0028] Mechanism of droplet osmotic regulation: The present invention, an intelligent mesh material that can adjust liquid permeability in real time, is essentially a composite mesh material, consisting of a mesh and cilia with magnetic response on its surface. The mesh structure allows liquid to pass through, and the flexible cilia can be instantly deflected at different angles under the action of magnetic force. The cilia in the natural state are vertically distributed on the surface of the mesh, and droplets can pass through the mesh; when a magnetic field is applied to the cilia, the cilia will deflect on the surface of the mesh, and the deflected cilia will cover the mesh and inhibit the passage of droplets. The deflection angle of the cilia is adjusted by changes in the magnetic field to change the porosity that can be penetrated by the liquid, thereby achieving continuous regulation of the mesh on liquid penetration.

[0029] Based on the above, compared with the prior art, the present invention has the following advantages:

[0030] Uniqueness of the liquid permeability regulation mechanism: In the present invention, the permeability of the grid is regulated by the deflection angle of the magnetically induced cilia under the action of the magnetic field. This mechanism for regulating liquid permeability is active, which is fundamentally different from the prior art method of changing the surface wettability or geometric structure of the grid.

[0031] Real-time regulation of liquid osmotic pressure: In the present invention, the regulation of liquid osmotic pressure is achieved by controlling the deflection of magnetically responsive cilia on the surface of the grid by means of a magnetic field. The response of cilia to the magnetic field is instantaneous, that is, the cilia-modified grid regulates liquid osmotic pressure in real time without hysteresis. This performance has not been demonstrated in other related inventions.

[0032] High efficiency of liquid permeability regulation: In the present invention, by controlling the magnetic field to change the deflection angle of the magnetically responsive cilia on the grid surface, a wide range of droplet permeability adjustment can be achieved, with the change value reaching as much as 5 times. According to currently known related technologies, the adjustable range of droplet permeability is only 0.56 times.

[0033] Preparation of smart mesh materials: In the present invention, the raw materials used in the preparation of the ciliary-modified grid and its hydrophobic modified solution can be directly customized or purchased, and the simple method of spraying is adopted, which makes the technology of the present invention have the advantages of simple method, time saving, and large-scale application.

[0034] The present invention proposes an intelligent mesh material that can adjust liquid permeability in real time, and has good application prospects in droplet atomization, cooling spray, fluid control, masks and functional textiles. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] FIG1 is a schematic diagram of the principle of the intelligent mesh material capable of adjusting liquid permeability in real time prepared in the embodiment and a physical display diagram of the sample, FIGa is a schematic diagram of the preparation of a mesh with magnetically responsive ciliary mesh modified on the surface, and FIGb is a display diagram of adjusting the mesh permeability by controlling the deflection of magnetically responsive ciliary meshes;

[0036] Figure 2 A flow chart for preparing a smart mesh material capable of adjusting liquid permeability in real time;

[0037] Figure 3 Demonstration of the dynamic process of liquid penetration control by smart mesh materials that can adjust liquid permeability in real time;

[0038] Figure 4 A schematic diagram of a test of the liquid penetration control function of the smart mesh material capable of adjusting liquid permeability in real time;

[0039] Figure 5 A data graph showing the penetration control of liquids dropped from different heights by a smart mesh material capable of adjusting liquid permeability in real time;

[0040] Figure 6 This is the microstructure array image when the cilia length in the smart mesh is 1.1 mm;

[0041] in, Figure 1a The bid number is:

[0042] 1——aluminum grid; 11——magnetically responsive cilia array;

[0043] 2 – Precursor solution;

[0044] 3 – Neodymium magnet;

[0045] 4——bracket; 5——spray gun; 6——air compressor. DETAILED DESCRIPTION

[0046] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0047] Metal aluminum sheet, thickness 0.2mm, commercial use, purchased from the market; NdFeB magnet, 0.38T, commercial use, purchased from the market; acetone, AR, Xilong Chemical Co., Ltd.; surfactant, Alcojet, ALCONOX; carbonyl iron powder, particle size 5~10um, McLean; PDMS 184, Dow Corning; 1H,1H,2H,2H-perfluorodecyltriethoxysilane, 96%, Aladdin; hydrophobic fumed silica, 7~40nm, 99.8%, Aladdin; 3-aminopropyltriethoxysilane (KH550), 98%, Aladdin; ethanol, 99.9%, Xilong Chemical Co., Ltd.

[0048] Infrared laser marking machine, HS50, Daju Group; ultrasonic cleaning machine, Azov, MCS-10; spray gun, LP-130K, Blue Brand; electric stirrer, OS20-S, Dalong; magnetic stirrer, MS7-H550-S, Dalong; electric heating blast drying oven, WGLL-65BE, Tianjin Test Instrument Co., Ltd.

[0049] Embodiment 1:

[0050] A smart mesh material that can adjust liquid permeability in real time Figure 2 Preparation steps shown:

[0051] Step 1: Use a laser marking machine to etch a metal aluminum sheet to obtain a grid with a hole size of 200um and a center distance of 400um between adjacent holes. Cut a 2.5cm×2.5cm sample and ultrasonically clean it in acetone and surfactant solution (0.5%) for 30min each, then rinse with deionized water and dry for later use;

[0052] Step 2: Add 7.5 g of carbonyl iron powder to 15 g of toluene solvent, perform ultrasonic dispersion treatment for 30 min at room temperature, and then mechanically stir for 20 min. Then, add 5 g of PDMS base liquid and 0.5 g of curing agent while stirring. After the addition is completed, continue stirring for 10 min to obtain a precursor solution.

[0053] Step three, such as Figure 1a As shown in the schematic diagram of the preparation of the surface modified with magnetic responsive ciliary grid, an aluminum grid 1 is horizontally placed on the surface of a neodymium magnet 3, a spray gun 5 is fixed on a bracket 4, the spray gun 5 is adjusted to spray vertically downward, the distance between the nozzle and the aluminum grid 1 is 30 cm, and the spray gun is provided with a pressure of 2 bar by an air compressor 6, 2.5 mL of the precursor solution is sprayed on the surface of the aluminum grid 1, and the curable polymer solution containing magnetic micro / nanoparticles grows directionally on the grid surface in a self-assembled manner along the magnetic induction lines under the action of the magnetic field, and finally forms a ciliary-like magnetic induction array structure; the obtained sample and the neodymium magnet 3 are placed in an oven at 60°C to remove the solvent and pre-cure for 60 minutes, and then the neodymium magnet 3 is removed, and the ciliary polymer array with magnetic responsive characteristics is cured for another 60 minutes at 120°C;

[0054] Step 4, add 0.2g 1H,1H,2H,2H-perfluorodecyltriethoxysilane, 0.1g KH550 and 0.1g hydrophobic fumed silica to 10g ethanol solvent respectively, stir mechanically for 30min and then ultrasonically treat for 30min at room temperature to obtain a hydrophobic modified solution, and use the spraying method to modify the surface of the solidified ciliary array to make it hydrophobic, and then dry it at 80°C for 60min to finally obtain a smart grid with a surface modified with a magnetic responsive ciliary array 11.

[0055] Embodiment 2:

[0056] An intelligent mesh material capable of adjusting liquid permeability in real time is prepared in the following steps similar to those in Example 1:

[0057] Step 1: Use a laser marking machine to etch a metal aluminum sheet to obtain a grid with a hole size of 200um and a center distance of 400um between adjacent holes. Cut a 2.5cm×2.5cm sample and ultrasonically clean it in acetone and surfactant solution (0.5%) for 30min each, then rinse with deionized water and dry for later use;

[0058] Step 2: Add 7.5 g of carbonyl iron powder to 15 g of toluene solvent, perform ultrasonic dispersion treatment for 30 min at room temperature, and then mechanically stir for 20 min. Then, add 5 g of PDMS base liquid and 0.5 g of curing agent while stirring. After the addition is completed, continue stirring for 10 min to obtain a precursor solution.

[0059] Step 3: Place a metal aluminum grid horizontally on the surface of a neodymium magnet, adjust the spray direction of the spray gun vertically downward, set the distance between the nozzle and the sample to 30 cm, set the spray gun pressure to 2 bar, spray 4 mL of the precursor solution on the grid surface, and allow the curable polymer solution containing magnetic micro / nanoparticles to grow directionally on the grid surface in a self-assembled manner along the magnetic induction lines under the action of the magnetic field, eventually forming a cilia-like magnetic induction array structure; place the sample and the magnet in an oven at 60°C to remove the solvent and pre-cure for 60 minutes, then remove the magnet and cure it at 120°C for another 60 minutes to obtain a cilia-like polymer array with magnetic response characteristics;

[0060] Step 4: Add 0.2 g 1H,1H,2H,2H-perfluorodecyltriethoxysilane, 0.1 g KH550 and 0.1 g hydrophobic fumed silica to 10 g ethanol solvent, stir mechanically for 30 min and then ultrasonically treat for 30 min at room temperature to obtain a hydrophobic modified solution. The surface of the solidified ciliary array is hydrophobically modified by spraying, and then dried at 80°C for 60 min to finally obtain a smart grid with a magnetically responsive ciliary array modified on the surface.

[0061] Embodiment three:

[0062] An intelligent mesh material capable of adjusting liquid permeability in real time is prepared in the following steps similar to those in Example 1:

[0063] Step 1: Use a laser marking machine to etch a metal aluminum sheet to obtain a grid with a hole size of 200um and a center distance of 400um between adjacent holes. Cut a 2.5cm×2.5cm sample and ultrasonically clean it in acetone and surfactant solution (0.5%) for 30min each, then rinse with deionized water and dry for later use;

[0064] Step 2: Add 7.5 g of carbonyl iron powder to 15 g of toluene solvent, perform ultrasonic dispersion treatment for 30 min at room temperature, and then mechanically stir for 20 min. Then, add 5 g of PDMS base liquid and 0.5 g of curing agent while stirring. After the addition is completed, continue stirring for 10 min to obtain a precursor solution.

[0065] Step 3: Place a metal aluminum grid horizontally on the surface of a neodymium magnet, adjust the spray direction of the spray gun vertically downward, set the distance between the nozzle and the sample to 30 cm, set the spray gun pressure to 2 bar, spray 6 mL of the precursor solution on the grid surface, and allow the curable polymer solution containing magnetic micro / nanoparticles to grow directionally along the magnetic induction lines on the grid surface in a self-assembled manner under the action of the magnetic field, eventually forming a cilia-like magnetic induction array structure; place the sample and the magnet in an oven at 60°C to remove the solvent and pre-cure for 60 minutes, then remove the magnet and cure at 120°C for another 60 minutes to obtain a cilia-like polymer array with magnetic response characteristics;

[0066] Step 4: Add 0.2g 1H,1H,2H,2H-perfluorodecyltriethoxysilane, 0.1g KH550 and 0.1g hydrophobic fumed silica to 10g ethanol solvent respectively, stir mechanically for 30min and then ultrasonically treat for 30min at room temperature to obtain a hydrophobic modified solution. The surface of the solidified ciliary array is hydrophobically modified by spraying, and then dried at 80°C for 60min to finally obtain a smart grid with a magnetically responsive ciliary array modified on the surface.

[0067] Experiments on the beneficial effects of smart grid products with magnetically responsive ciliary arrays on their surfaces:

[0068] According to the above examples 1, 2 and 3, intelligent mesh materials with ciliary lengths of 0.5 mm, 1.1 mm and 1.6 mm for liquid permeation regulation were prepared respectively. Figure 3 As shown, the legends A, B and C correspond to the dynamic process of liquid penetration regulation of smart grids with ciliary lengths of 0.5mm, 1.6mm and 1.6mm respectively under the action of a magnetic field. Here, the droplet is released from a height of 30cm and impacts the surface of the smart grid material after free fall, corresponding to an impact velocity of 2.4m / s. By adjusting the magnetic field, the deflection angles of the 0.5mm and 1.6mm cilia are both 0°, that is, the cilia are vertically upward. Cilia with a length of 1.6mm will cause less liquid penetration. Most importantly: when the cilia (1.6mm) are deflected at an angle of 70°, only one droplet penetrates the grid. The visualized dynamic process confirms that liquid penetration (or grid permeability) can be adjusted in real time by changing the deflection angle of the cilia through the action of a magnetic field.

[0069] To verify the high efficiency of the smart grid in regulating liquid penetration, a systematic quantitative experiment was conducted on the permeability after droplet impact. The penetration quality was confirmed by weighing the amount of penetrating liquid captured by the collector, which is a lightweight copper plate placed under the grid. The entire measurement system is as follows Figure 4As shown. In order to reduce the uncertainty of the measurement, 12 droplets are continuously dropped at different positions on the grid surface within one minute, and then the total amount of liquid that penetrates is weighed. Here, the release height of the droplet ranges from 30cm to 90cm, and the corresponding impact velocity ranges from 2.4m / s to 4.2m / s. The penetration of the droplet is expressed as the penetration ratio, that is, the mass of the penetrating droplet divided by the initial droplet mass.

[0070] The results of the smart grid with different lengths of cilia on the osmotic regulation of droplets are shown in Figure 2. Figure 5 Therefore, here we only show the control effect of the four states of ciliary tilt angles of 0°, 30° and 70° under the action of a magnetic field and without a magnetic field on droplet penetration. From the data, it can be seen that regardless of the grid structure, the droplet penetration rate will decrease with the increase of ciliary length. This is mainly because the impact velocity used for droplet penetration is blocked by the friction loss of cilia. Importantly, despite the difference in ciliary length and droplet falling height, a larger ciliary tilt angle will result in a smaller droplet penetration rate, which is consistent with Figure 3 This is consistent with the droplet penetration dynamics visualization results in . This is mainly because the cilia at larger tilt angles can cover more pores. Figure 3 and Figure 5 The experimental results confirmed that the magnetically responsive cilia-modified grid of the present invention can achieve the function of regulating liquid permeability in real time and efficiently.

[0071] Figure 6 The following are the actual pictures of the smart grid with a ciliary length of 1.1 mm and the display of magnetic response adjustment. Figures ac are the actual pictures of the ciliary deflection of 0°, 30° and 70° under the action of the magnetic field, and Figures d and f respectively show the good hydrophobicity of the ciliary surface and the coverage effect of the mesh when the ciliary inclination angle is 0° and 70°. When the cilia are perpendicular to the grid, that is, when the deflection angle β=0°, there is no coverage effect on the mesh; when β=70°, most of the mesh holes of the grid are covered.

[0072] The above are only specific embodiments of the present invention and are not intended to limit the protection scope of the present invention.

Claims

1. A smart mesh material capable of adjusting liquid permeability in real time, characterized in that: The grid material is used as the substrate, and its surface is modified with a magnetically responsive cilia array. The magnetic field is used to control the inclination of the cilia on the grid surface and thus adjust the porosity through which the droplets can pass, thereby achieving real-time control of liquid penetration. The length of the magnetically responsive cilia is 500-3000um, the diameter is 30-200um, and the distance between the tips of two adjacent cilia is 30-700um; In their natural state, cilia are distributed vertically on the surface of the grid, and droplets can pass through the mesh holes. When a magnetic field is applied to the cilia, the cilia will deflect on the surface of the grid. The deflected cilia will cover the mesh holes and inhibit the passage of droplets. The porosity that can be penetrated by liquid is changed by adjusting the deflection angle of the cilia through changes in the magnetic field, thereby achieving continuous adjustment of the grid to liquid penetration and real-time control.

2. The intelligent mesh material capable of adjusting liquid permeability in real time according to claim 1, characterized in that: The magnetically responsive cilia are curable polymers wrapped with magnetic micro / nano particles. The polymer cilia formed after curing and molding have a hydrophobic modified coating on the surface of the cilia.

3. The intelligent mesh material capable of adjusting liquid permeability in real time according to claim 2, characterized in that: The magnetic micro / nano particles are carbonyl iron powder particles, carbonyl cobalt particles or other particles with magnetic response characteristics, and the particle size is not greater than 20um.

4. The intelligent mesh material capable of adjusting liquid permeability in real time according to claim 2, characterized in that: The curable polymer is one or more than two of polydimethylsiloxane (PDMS), polyimide (PI), and polyurethane elastomer (TPU) viscoelastic polymers.

5. The intelligent mesh material capable of adjusting liquid permeability in real time according to claim 1, characterized in that: The mesh material is one of the rigid mesh materials including laser processed or commercial aluminum mesh, copper mesh, and stainless steel mesh.

6. The intelligent mesh material capable of adjusting liquid permeability in real time according to claim 1, characterized in that: The mesh material is a polymer mesh film.

7. The intelligent mesh material capable of adjusting liquid permeability in real time according to claim 1, characterized in that: The mesh material is a fiber mesh membrane.

8. The intelligent mesh material capable of adjusting liquid permeability in real time according to claim 1, characterized in that: Flexible fabric mesh material.

9. The intelligent mesh material capable of adjusting liquid permeability in real time according to claim 1, characterized in that: The mesh morphology of the mesh material is circular, square, or triangular. The pores allow droplets to penetrate. The diameter of the pores and the distance between the geometric centers of two adjacent pores are 100 to 1000 um.

10. A method for preparing a smart mesh material capable of adjusting liquid permeability in real time according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: Step 1, mesh material preparation: the mesh material is ultrasonically cleaned with acetone and surfactant solution to remove surface impurities and oil stains, and then cleaned with deionized water and dried for use; Step 2: Prepare a curable polymer solution of magnetic micro / nanoparticles as a precursor solution: add 7.5 g of magnetic micro / nanoparticles to 15 g of solvent, perform ultrasonic dispersion treatment for 30 min at room temperature and then mechanically stir for 20 min, then add 5 g of curable polymer while stirring, and continue stirring for 10 min after the addition to obtain a precursor solution; Step 3: Place the grid material obtained in step 1 horizontally on the surface of the magnet, spray the prepared precursor solution on the surface of the grid material by spraying, the distance between the nozzle and the sample is 5-50 cm, the spraying pressure is 1-5 bar, and the curable polymer solution containing magnetic micro / nanoparticles grows directionally along the magnetic induction lines on the grid surface in a self-assembled manner under the action of the magnetic field, so as to obtain a sample with a cilia-like magnetic induction array structure formed on the grid surface; place the sample and the magnet in an oven at 60°C to remove the solvent and pre-cure for 60 minutes, then remove the magnet, and cure the finalized sample at 120°C for 60 minutes, so that a magnetic responsive cilia array grows on the surface of the grid material; Step 4, hydrophobically modify the magnetically responsive ciliary array obtained in step 3: add 0.2g of fluorinated silane, 0.1g of silane coupling agent and 0.1g of hydrophobic nanoparticles to 10g of organic solvent respectively, mechanically stir for 30min and then ultrasonically treat for 30min at room temperature to obtain a hydrophobic modified solution, use a spraying method to hydrophobically modify the surface of the magnetically responsive ciliary array, and then dry at 80°C for 60min to finally obtain an intelligent mesh material with a surface modified with a magnetically responsive ciliary array.

11. The method for preparing the intelligent mesh material capable of adjusting liquid permeability in real time according to claim 10, characterized in that: In step 2, the solvent is one of toluene, dichloromethane, chloroform and n-hexane.

12. The method for preparing the intelligent mesh material capable of adjusting liquid permeability in real time according to claim 10, characterized in that: In step three, the magnet is a permanent magnet of neodymium iron boron, samarium cobalt, or aluminum nickel cobalt, and is in the shape of a rectangular parallelepiped, a cube, or a cylinder, with a magnetic induction intensity of 0.1 to 2 T; when the spraying method is adopted, the angle between the nozzle direction and the horizontal plane of the sample is 0 to 90°, the distance between the nozzle and the sample is 5 to 50 cm, the spraying pressure is 1 to 5 bar, and the spraying volume is 2 to 10 mL.

13. The method for preparing the intelligent mesh material capable of adjusting liquid permeability in real time according to claim 10, characterized in that: In step 4, in the hydrophobic modified solution, the hydrophobic nanoparticles are one of silicon dioxide, titanium dioxide, aluminum oxide and zinc oxide, and the particle size is 5 to 500 nm; the fluorinated silane is 1H, 1H, 2H, 2H-perfluorodecyltrimethoxysilane, 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane, trimethoxy (1H, 1H, 2H, 2H-perfluoro-1-octyl) silane and triethoxy(1H,1H,2H,2H-perfluoro-1-octyl)silane; the silane coupling agent is one of 3-aminopropyltriethoxysilane (KH550), 3-(2;3-epoxypropoxy)propyltrimethoxysilane (KH560) and N-[3-(trimethoxysilyl)propyl]ethylenediamine (KH792); the organic solvent is one of ethanol, propanol, ethyl acetate and toluene.

Citation Information

Patent Citations

  • Humidity sensing self-regulated fabric and preparation method thereof

    CN109371680A

  • Waterproof breathable composite net, and preparation method and application thereof

    CN113665194A

  • Breathable fabrics with smart pores

    US11122846B2

  • Temperature and moisture responsive smart textile

    US20080057809A1

  • Smart porous film or material

    US6770579B1